NONSTEROIDAL ANTI-INFLAMMATORY DRUGS: CURRENT ASPECTS OF THEIR USE - N. A. Shostak; A. A. Klimenko (Klinicist, 2014)
The paper shows the basic mechanisms of action of nonsteroidal antinflammatory drugs (NSAID) and their classification. It considers riskfactors for NSAID gastropathy and the possibilities of its treatment, prevention in the context of modern medicine.